(untitled) (TAMADDUN NURI JURNALI, 2025)
This paper is dedicated to the poetics of fear as one of the possible aspects of comparing Chekhov’s world with Turgenev’s, based on the analysis of Chekhov’s short story Panic Fears (1886) and the parallels between it and Turgenev’s The Dog (1866). Other parallels linked to the poetics of fear in the two writers’ works are mentioned only as the possibility of more extensive investigations.